Stem Cells - Bosch, Thomas C. G. (Springer, 2017)
Much of our knowledge of stem cells has been inferred from studies of remarkable few species. The ability to manipulate stem cells in “model” organisms such as the mouse and a few other vertebrate species has driven our understanding of basic biology of stem cells. The power and efficiency of studying model organisms, however, comes at a cost since a few species, obviously, do not reflect nature´s true diversity. Unfortunately, although all multicellular organisms seem to rely on stem cells, and although this seems to be a question of key importance for understanding the evolution of animal life, little is known about stem cells in early-branching taxa.